Effect of Sunlight and Ultraviolet Light on Dissipation of Fipronil Insecticide in Two Soils and Effect of pH on its Persistence in Aqueous Medium. Issue 7 (January 2014) - Verma, Ankita; Srivastava, Anjana; Chauhan, Shailendra Singh; Srivastava, Prakash Chandra
In a laboratory investigation, the effect of natural sunlight and UV light exposure on dissipation of fipronil insecticide from two soils (clay loam and sandy clay loam) and the effect of pH on the persistence of fipronil in aqueous medium were studied. Dissipation of fipronil insecticide under sunlight followed biphasic first order kinetics in both soils. The half-life of the insecticide in sandy clay loam type soil was found to be 5.71 days for the first faster phase and 23.88 days for the second slower phase, whereas, in clay loam soil, the corresponding half-lives were 4.02 and 8.38 days, respectively. Under the UV light exposure, the dissipation of fipronil followed a single phase first order kinetics in both the soils with a half-life of 3.77 days in clay loam and 5.37 days in sandy clay loam, respectively. Residues of fipronil dissipated faster in clay loam than in sandy clay loam under both sunlight and UV lamp light. As compared to sunlight, dissipation was found to be faster under UV lamp light. Persistence of fipronil in aqueous medium under different pH conditions revealed that fipronil residues were below the limit of detection (LOD), <0.05 μg g −1, after 40 days of sampling at all the three pH. The dissipation of fipronil from aqueous medium increased with increasing pH from 5.0 to 9.0; the corresponding half-lives were 14.12, 9.83, and 6.76 days at pH 5.0, 7.0, and 9.0, respectively.